Modal deflection method for bridge load testing: a practical alternative to static load tests - Shukun Li; Sheng Qi; Ruofan Zhao; Xingjun Qi; Sanpeng Cao (Građevinar)
This study investigated the effectiveness of modal deflection testing as a substitute for static load tests, focusing on the separation of the Ji-Jiao railway separated overpass. The designed load test schemes for both the central and eccentric loading conditions were used to measure the real-time static deflections of the bridge to assess its bearing capacity. Modal testing based on ambient excitation was employed to capture the acceleration vibration responses and identify the key modal parameters of the bridge. The Kriging interpolation method was utilised to extend the mode shapes along both the longitudinal and transverse directions of the bridge deck. The flexibility matrix of the main beam was computed, the modal deflections of the bridge under static test vehicle loads were predicted, and a comparative analysis was conducted using the measured static deflections from the static load test. The results showed that the modal deflections at the midspan section closely matched the static deflections, with errors consistently below 10%. This suggests that modal testing can effectively replace static load tests, providing a viable method for assessing the bridge load-bearing status and enabling real-time health monitoring. This achievement has practical engineering value and opens up prospects for future research.